Discontinuation of Systematic Surveillance and Contact Precautions for Vancomycin-Resistant Enterococcus (VRE) and Its Impact on the Incidence of VRE faecium Bacteremia in Patients with Hematologic Malignancies. (11th January 2016) - Almyroudis, Nikolaos G.; Osawa, Ryosuke; Samonis, George; Wetzler, M.; Wang, Eunice S.; McCarthy, Philip L.; Segal, Brahm H.
Abstract : OBJECTIVE: To study the effect of discontinuation of systematic surveillance for vancomycin-resistant Enterococcus (VRE) and contact isolation of colonized patients on the incidence of VRE bacteremia SETTING: A hematology-oncology unit with high prevalence of VRE colonization characterized by predominantly sporadic molecular epidemiology PARTICIPANTS: Inpatients with hematologic malignancies and recipients of hematopoietic stem cell transplantation METHODS: The incidence of VRE bacteremia was measured prospectively during 2 different 3-year time periods; the first during active VRE surveillance and contact precautions and the second after discontinuation of these policies. We assessed the collateral impact of this policy change on the incidence of bacteremia due to methicillin-resistant Staphylococcus aureus (MRSA) and Clostridium difficile infection even though we maintained contact precautions for these organisms. Incidence of infectious events was measured as number of events per 1, 000 patients days per month. Time series analysis was used to evaluate trends. RESULTS: The incidence of VRE bacteremia remained stable after discontinuation of VRE surveillance and contact precautions. The incidence of MRSA bacteremia and Clostridium difficile infection for which we continued contact precautions also remained stable. Aggregated antibiotic utilization and nursing hours per patient days were similar between the 2 study periods. CONCLUSION: Active surveillance and contact precautions for VRE colonization did not appear to prevent VRE bacteremia in patients with hematologic malignancies and recipients of hematopoietic stem cell transplantation with high prevalence of VRE characterized by predominantly sporadic molecular epidemiology. Infect. Control Hosp. Epidemiol. 2016;37(4):398–403